Melatonin mediates the BMP4/MAPK signaling pathway to alleviate zearalenone-induced abnormal embryonic development in mice - Mengyao Wang; Zhixin Pu; Jing Zhang; Peiwen Wang; Yaxin Chen; Yating Zhu; Hongzhen Ruan; Dongmei Ji; Weiwei Zou; Huiru Cheng; Zhiming Ding; Yunxia Cao; et al. (Ecotoxicology and Environmental Safety)
Zearalenone (ZEA) is a common mycotoxin found in crops that poses a threat to human health, particularly the female reproductive system. Here, we show that exposing mouse zygotes to ZEA in vitro significantly impairs embryo development, leading to embryo arrest. Remarkably, treatment of ZEA-exposed mouse embryos with melatonin significantly improved the blastocyst rates from approximately 40 % to nearly 80 %. Furthermore, melatonin effectively mitigates the harmful effects of ZEA exposure by reducing reactive oxygen species (ROS) levels, preventing mitochondrial dysfunction, and decreasing cell apoptosis. Following embryo transplantation, the birth rate of offspring increased markedly from 7.2 % to 23.62 %. Further research revealed that the abnormal elevation of bone morphogenetic protein 4 (BMP4) signaling induced by ZEA exposure, coupled with the inhibition of the downstream mitogen-activated protein kinase (MAPK) signaling pathway, contributes to developmental blockade in ZEA-exposed mouse embryos. Melatonin rescued ZEA-induced defects in mouse embryo development by inhibiting BMP4 signaling and regulating the MAPK pathway. Moreover, the Bmp4 inhibitor Noggin or its receptor inhibitor DMH-1 could also effectively ameliorate the ZEA-induced impairment of embryo development. Taken together, these findings underscore the potential of melatonin as a therapeutic intervention for addressing the adverse effects of ZEA exposure on mouse embryos.